Effects of Cognitive–Behavioral Conjoint Therapy for PTSD on Partners' Psychological Functioning. Issue 2 (4th April 2014) - Shnaider, Philippe; Pukay‐Martin, Nicole D.; Fredman, Steffany J.; Macdonald, Alexandra; Monson, Candice M.
Abstract: A number of studies have documented that posttraumatic stress disorder (PTSD) symptoms in "one" partner are negatively associated with their intimate partner's psychological functioning. The present study investigated intimate partners' mental health outcomes (i.e., depression, anxiety, and anger) in a sample of 40 partners of individuals with PTSD within a randomized waitlist controlled trial of cognitive–behavioral conjoint therapy for PTSD (Monson & Fredman, 2012 ). There were no significant differences between active treatment and waitlist in intimate partners' psychological functioning at posttreatment. Subgroup analyses, however, of partners exhibiting clinical levels of distress at pretreatment on several measures showed reliable and clinically significant improvements in their psychological functioning at posttreatment and no evidence of worsening. Results suggest that cognitive–behavioral conjoint therapy for PTSD may have additional benefits for partners presenting with psychological distress.